Copolymerization of carbon dioxide and propylene oxide catalyzed by two kinds of bifunctional salen‐cobalt(III) complexes bearing four quaternary ammonium salts. Issue 1 (4th July 2019) - Du, Longchao; Wang, Chengze; Zhu, Weiju; Zhang, Jie
Abstract: Two new bifunctional salen‐cobalt(III) complexes were synthesized, which consist of salicylaldehyde bearing four quaternary ammonium salts and two different diamines. The copolymerization results indicated that decreasing temperature is advantageous for both the complexes. Of both the diamines, the complex 9 with o ‐diaminobenzene has a higher catalytic effect compared to complex 6 with 1, 2‐diaminocyclohexane. The catalytic effect of complex 9 is over 3.5 times than that of complex 6 at a temperature of 30°C. The research of P CO2 on the copolymerization revealed that the first‐rank pressure was at 2 MPa for the two complexes. The highest turnover number are under conditions of T = 30°C, P CO2 = 2 MPa, and t = 24 hr. Differential scanning calorimeter curves indicated that poly(propylene carbonate) (PPC) by complex 9 has the highest Tg of 54.2°C. DTGA curves showed that there were two thermal degradation peaks, the first is for the ester bond, and the second is for the C–C bond. Abstract : Two new bifunctional salen‐cobalt(III) complexes were synthesized, and a detailed study on the mechanism for the copolymerization of CO2 and propylene oxide (PO) was performed. The complex 9 with o ‐diaminobenzene has a higher catalytic effect compared to complex 6 with 1, 2‐diaminocyclohexane. The highest turnover number (TON) for the two complexes are under conditions of T = 30°C, P CO2 = 2 MPa, and t = 24 hr.